The convergence of endosomal and autophagosomal pathways: Implications for APP-CTF degradation - Tian, Yuan (Landes Bioscience, 2014)
We have reported previously that autophagy is responsible for amyloid precursor protein-C-terminal fragment (APP-CTF) degradation and therefore Aβ clearance. To elucidate the underlying mechanism, using LC3 affinity purification and mass spectrometry analysis, immunoprecipitation (IP), as well as live imaging analysis, we identified and demonstrated that the adaptor-related protein complex 2 (AP2) and PICALM (phosphatidylinositol binding clathrin assembly protein) are in a complex with LC3 and APP-CTF. Taken together, this new set of data suggests that the AP2-PICALM complex functions as an autophagic cargo receptor for the recognition and shipment of APP-CTF from the endocytic pathway to the LC3-dependent autophagic degradation pathway. Interestingly this AP2-LC3 connection seems to be involved in chemically-induced APP-CTF clearance as we observed using the small compound SMER28. The effect observed following SMER28 was significantly reduced after silencing AP2. While more work is required to elucidate the detailed molecular mechanisms involved, our actual data suggest that there is some level of specificity in the steps mentioned above.